Planejamento sucessório no agronegócio e suas particularidades - Truzzi, Líbera Copetti de Moura (2025)
Agribusiness is one of the segments with the highest national economic growth, responsible for almost 24% of the GDP and more than 50% of all the value exported in the country. In addition to its important economic characteristic and the undoubted social impacts that agribusiness exerts, the activity has a relevant characteristic: it is a predominantly family activity, with more than 80% of rural establishments in Brazil characterized as family establishments, which belong to and are managed by one or more members of the same family, which legal regime of exploitation is mostly based on the individual regime. These characteristics add different perspectives to the activity and consequently to succession planning. The absence of patrimonial and succession treatment may cause several obstacles to the maintenance and survival of the productive activity, especially in the face of a litigious probate process, making succession planning a fundamental element for these families, given their family characteristics and situations. The objective of this study is to analyze succession planning in agribusiness from the perspective of the particularities of the activity and the respective impacts that these particularities can promote in the conduct and in the choice of the most common types of planning instruments. Under the cut of the activities called inside the gate, the particularities most present in the activity in general are analyzed, starting with its family element; its agrarianity; legal regimes of exploitation; issues related to the nature of rural real estate; environmental issues; issues related to typical agrarian contracts, among others. Through deductive methodology, the study analyses in a multidisciplinary way the inferences that such particularities can promote in planning. It was found through the research that the use of generic criteria and the non-observance of these elements can lead to the failure of the planning. It was found that the use of different planning instruments should be functionalized to the activity and its particularities. Likewise, it was found that the family characteristic of the activity represents the central basis of planning in agribusiness, aligned with the particularities and purposes of the parties involved, which instruments should be functionalized to the particular needs and realities of each family nucleus, from the personal perspective of each member that makes up the family nucleus, as a prerequisite for efficient succession planning. Considering that it is an activity with multiple and heterogeneous characteristics, other layers, especially the particularities presented, should compose the planning framework from the perspective of agribusiness, and it is not possible to generalize or establish an ideal planning instrument, but rather a set of legal measures analyzed in a judicious and individualized manner